Exploring North Carolina Family and Consumer Sciences Teachers' Attitudes Towards Breastfeeding and Infant Feeding Education Practices. (November 2020) - Singletary, Nicola; Goodell, L. Suzanne; Fogleman, April
Background: The World Health Organization (WHO) and the United Kingdom Committee for UNICEF recommend that secondary schools include infant feeding education in the curriculum. However, little attention has been given to the study of educators' views and practices regarding infant feeding education. Aims: The aims of this research were to (1) explore North Carolina Family and Consumer Sciences teachers' attitudes towards infant feeding education in secondary schools and (2) describe North Carolina Family and Consumer Sciences teachers' infant feeding education practices. Methods: Researchers conducted interviews ( N = 19) and a survey ( N = 137) using a sequential mixed methods design. The constant comparative method was used to analyze interview transcripts. Subsequently, a 33-item survey was developed to assess teachers' attitudes and practices, and this survey was tested for validity and reliability. Results: The majority of participants supported including infant feeding ( n = 119, 86.9%) and breastfeeding ( n = 116, 84.7%) education in high school. Approximately half of the participants supported including infant feeding ( n = 71, 51.9%) and breastfeeding ( n = 64, 46.7%) education in middle school. Participants reported that they taught infant feeding at both levels; topics taught included complementary foods, patterns of infant feeding, and the safe preparation of infant formula. Breastfeeding content was covered primarily in the high school Parenting and Child Development course. Conclusions: North Carolina Family and Consumer Sciences teachers have positive attitudes towards teaching about breastfeeding at the secondary school level. Content about infant nutrition and breastfeeding is currently included in courses that cover child development and human nutrition.